Symbolic heart rate transition motifs during nocturnal sleep are associated with diabetic complications in type 2 diabetes - Namareq Widatalla; Sona Al Younis; Samit Kumar Ghosh; Ahsan Khandoker (PLoS ONE, 2025)
Dysfunction in the autonomic nervous system function during sleep is common in type 2 diabetes mellitus and is associated with increased risk of diabetic related complications. While heart rate variability is a standard non-invasive measure of autonomic function, the utility of symbolic heart rate transition motifs to characterize sleep-specific autonomic dysfunction in diabetes has not been explored. Here, we analysed 5-min electrocardiogram segments during daytime and sleep from 35 male participants ((51 ± 17) years old) with type 2 diabetes mellitus. Frequency-domain heart rate variability metrics and 27 symbolic motifs based on 3-beat heart rate transitions were computed. Logistic regression models adjusted for age and body mass index were used to test associations with diabetic complications. The high frequency power of heart rate variability was significantly higher during sleep than daytime (p = 0.012), reflecting enhanced parasympathetic activity. Several symbolic motifs showed differential prevalence between sleep and day. In particular, motif [1, 1, −1] was significantly more prevalent during sleep and was independently associated with diabetic complications (β = −1.8, p = 0.023). Motif [1,1,-1] along with [−1, 1, 1], showed strong positive correlations with high frequency power during day and sleep [Day: [1,1,-1]: r = 0.70 (p = 7.0e-06), [−1,1,1]: r = 0.78 (p = 4.5e-07)] [Sleep: [1,1,-1]: r = 0.77 (p = 5.7e-07), [−1,1,1]: r = 0.80 (p = 3.1e-07)], suggesting a link to vagal tone. The study’s findings provide a novel, non-invasive approach to sleep-based autonomic monitoring in type 2 diabetes mellitus by showing that the symbolic heart rate motifs during sleep reflect unique autonomic patterns associated with diabetic complications. These results demonstrate the diagnostic utility of motif-based HR analysis for diabetes and sleep medicine.